Twin parenthood: the midwife's role – a randomised controlled trial. (19th May 2014) - Carrick‐Sen, DM; Steen, N; Robson, SC
Abstract : Objective: To determine whether a midwife‐led intervention improved preparation for twin parenting and maternal psychosocial outcome. Design: Randomised controlled trial. Setting: Two maternity units in North East England. Population: A cohort of 162 women with uncomplicated twin pregnancy. Methods: Self‐completion questionnaire at multiple time points. Main outcome measures: The primary outcome was probable postnatal depression (measured with the Edinburgh Postnatal Depression Scale, EPDS) 26 weeks after delivery. Secondary outcomes included preparation for parenting, maternal anxiety, parenting stress, and maternal wellbeing. Results: The mean maternal EPDS scores at 26 weeks after delivery were 5.4 (SD 4.5) in the twin intervention (TI) group and 6.9 (SD 5.5) in the twin control (TC) group, and the mean difference between the groups was 1.5 (95% confidence interval, 95% CI, −0.2 to 3.3). The relative risk (RR) of having probable depression in the TI group compared with the TC group at 26 weeks was 0.48 (95% CI 0.19–1.20) for mothers and 0.84 (95% CI 0.42–1.70) for fathers. There were no statistically significant differences in maternal anxiety or parenting stress. TI mothers reported increased maternal wellbeing, reaction to motherhood, family support, mood, and greater self‐confidence 26 weeks after delivery, and felt more prepared for parenting. Conclusion: As a result of the limited sample size, the study was unable to detect a difference in maternal depression using the maternal EPDS mean score. The antenatal preparation for parenting programme did not improve postnatal maternal anxiety or parenting stress; however, it did improve postnatal maternal wellbeing, mood, self‐confidence, reaction to motherhood, and better prepared mothers to parent twin infants. Midwives have a key role in preparing mothers to parent twins.